Predisposing and enabling factors associated with Venezuelan migrant and refugee women's access to sexual and reproductive health care services and contraceptive usage in Peru - Rossmary D. Márquez-Lameda (Elsevier, 2022)
Objective: Over 6 million migrants and refugees from Venezuela have left their country in the past decade; 1 million of them reside in Peru. Venezuelan migrant and refugee women are known to have limited access to sexual and reproductive health care services (SRHS) and contraceptive usage. To date, research to understand factors influencing access to those services is limited. This study aims to determine which enabling and predisposing factors influence Venezuelan migrant and refugee women's access to SRHS and contraceptive usage. Methods: This is a retrospective cross-sectional study of the first survey administered to the Venezuelan population residing in the Peru in 2018. The survey covered six cities in the country (Metropolitan Lima, Callao, Tumbes, Cusco, Trujillo, Arequipa). The sample for the study included Venezuelan migrant women of reproductive age (15-49 years old). Anderson's Behavior Model of Health Services is the conceptual framework of the investigation. Logistic regression models were fit to examine the relationship between different predisposing and enabling factors and women's access to SRHS and contraceptive usage. Results: The sample size includes a total of 3378 Venezuelan women of reproductive age. 50.7% of the women were between the ages of 21-30 and over 90.6% of the sample were residing in Metropolitan Lima. Only 20.2% of the women reported they had access to modern contraceptives. Results from the study suggest having insurance, residing in Trujillo, and having a higher socio-economic status were associated with more access to certain sexual reproductive health care services and contraceptive usage. Conclusion: This study identified different predisposing and enabling factors relevant to the access to SRHS and contraceptive usage. Difference in access and usage are particularly pronounced based on insurance status, geographical location, and socio-economic status. Displaced Venezuelans will remain abroad for an extended period of time, if not permanently. Focus should shift from providing humanitarian aid to integrating the migrants and refugees, particularly the most vulnerable groups, into the local economic and healthcare system.